The associations between workplace bullying, salivary cortisol, and long-term sickness absence: a longitudinal study - Matias Brødsgaard Grynderup; Kirsten Nabe-Nielsen; Theis Lange; Paul Maurice Conway; Jens Peter Bonde; Anne Helene Garde; Maria Gullander; Linda Kaerlev; Roger Persson; Reiner Rugulies; Marianne Agergaard Vammen; Annie Høgh; et al. (BMC, 2017)
Abstract Background Workplace stressors, such as bullying, are strongly related to subsequent long-term sickness absence, but little is known of the possible physiological mechanisms linking workplace stressors and sickness absence. The primary aim of this study was to investigate to what extent cortisol levels were associated with subsequent sickness absence and if cortisol mediated the association between workplace bullying and sickness absence. We additionally investigated possible bidirectional associations between bullying, cortisol, and long-term sickness absence. Methods Participants came from two Danish cohort studies, the "Psychosocial RIsk factors for Stress and MEntal disease" (PRISME) cohort and the "Workplace Bullying and Harassment" (WBH) cohort (n = 5418). Information about exposure to workplace bullying and morning and evening salivary cortisol was collected at three time points with approximately two years in between. After each data collection, all participants were followed for two years in registers, and cases with long-term sickness absence lasting 30 or more consecutive days were identified. The association between cortisol levels and subsequent sickness absence was assessed by logistic regression, while the extent to which the association between bullying and sickness absence was mediated by cortisol was quantified through natural direct and indirect effects. Results High evening cortisol was associated with a decreased risk of sickness absence (OR = 0.82, 95% CI = 0.68-0.99), but we did not find that high morning cortisol levels (OR = 0.98, 95% CI = 0.81-1.18) or high morning-to-evening slope (OR = 0.99, 95% CI = 0.82-1.18) were associated with subsequent sickness absence. We also tested for reverse causation and found that long-term sickness absence, but not salivary cortisol, was a strong risk factor for subsequent workplace bullying. There was no indication that cortisol mediated the association between workplace bullying and sickness absence. Conclusion We found no straightforward and simple association between cortisol and long-term sickness absence. Furthermore, the association between workplace bullying and long-term sickness absence was not mediated by cortisol.